Public Perceptions of Human Trafficking in Moldova - Jill Robinson (Psychosocial Intervention, 2011)
Human trafficking is a widely studied phenomenon. Comparing public perceptions of trafficking to institutional (i.e. the academy, governmental and non-governmental organizations) perceptions gives a richer understanding of the problem. The data for this study were collected in and around Chisinau, Moldova in the summer of 2004. Public discourse provides a more intimate "portraiture" of the issue, but the public also demonstrated a complex level of understanding of this social problem in this study. Its view is juxtaposed against an institutional view of human trafficking as explored through a literature review. Combining institutional and public perceptions and knowledge of a social problem is helpful in not only establishing a more thorough understanding of the social problem and guiding policy decisions, but in exploring the experiences victims may face at the community level.